Теплообмін із повітрям плівки рідини, що стікає пласкою поверхнею зі сферичними заглибленнями - Dubrovskyi V.V.; Pidvysotskyi O.M.; Shraiber O.A. (General Energy Institute of the National Academy of Sciences of Ukraine, 2008)
We have performed an experimental study of the heat transfer of a liquid film flowing over a flat surface with spherical indentations with air. We have established that using profiled surfaces enables one to enhance significantly (trice and even more) the heat transfer intensity.